KINETICS OF REACTIONS ACRYLONITRILE SECONDARY AMINE IN WATER–1,4-DIOXANE MIXTURES (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
Summary Kinetics of the reactions acrylonitrile (AN)–secondary amine [piperidine (PP), morpholine (Mph), diethylamine (DEA), dipropylamine (DPA) and dietanolamine (DEolA)] has been studied in aqueous solutions and water–1,4-dioxane mixtures, using UV-spectroscopic and dilatometric methods at 298 K. It has been shown, that for all studied couples the reaction law is: W = K[AN] [Amine]. A correlation between reactions’ rate constants and the product of ionization potential (I) with amine’s basicity (pKb) has been established. It has been shown, that with increase of water fraction in water–1,4-dioxane mixtures the rate of AN–secondary amine reaction increases. Influence of medium on the AN–secondary amine reaction rate, taking into account medium viscosity, dielectric constant, refraction index, electrophility and nucleophility of water and 1,4-dioxane has been discussed.